PENGARUH KETERAMPILAN MENGAJAR GURU DAN AKTIVITAS BELAJAR TERHADAP HASIL BELAJAR SISWA MATA PELAJARAN KEWIRAUSAHAAN DI SMK DAREL HIKMAH PEKANBARU - Elfika, Cici; Gimin, Gimin; Haryana, Gani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to determine the effect of teachers teaching skills and learning activities on student learning outcomes of entrepreneurship subjects in SMK Darel Hikmah Pekanbaru. The population in this study were students of class X and XI TI and PS which amounted to 59 people, the sample was obtained by using simple random sampling method as much as 52 respondents. Data analysis method used is multiple linear regression analysis. The result of this research is the skill of teaching the teacher does not have a significant effect on the student's learning result which is obtained tcount 0,091 <ttabel 2,009 and significant value 0,928> 0,05. Learning activities have a positive and significant impact on student learning outcomes where obtained tcount 2,991> ttabel 2,009 and significant value 0,004 <0,05. In silmutan there is a positive or significant influence between teacher's teaching skills and student learning activities with learning results fcount 11.086> ftabel 3.18 and significant value 0,000 <0.05. The result of multiple regression research found that the skills of teaching teachers and learning activities have a significant effect on the students' learning outcomes of 27.1% of the learning outcomes and the rest of 72.9% influenced by other factors outside this study. Multiple regression equation obtained in this research is Y1 = 43,107 + 0,010 X1 + 0, 428 X2. This means that if the skills of teaching teachers (X1) and learning activities (X2) does not exist then the amount of learning outcomes (Y) of 43.107 and any increase in skills of teaching teachers will increase student learning outcomes by 0.010 and any increase in learning activities it will improve student learning outcomes of 0.428.Keywords: Teacher Teaching Skills, Learning Activity and Learning Outcomes